Development of Short Story Module Based on Interpersonal Intelligence for SMA/MA Grade XI Students - Muhamad Fajar Rizkia (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Learning process expected to use any kind of source and media that support study activity and suitable with students’ characteristics. However, use of teaching materials are limited because of some factors such as availability, completeness and also it is not based on needs of students which aimed to certain development of intelligence yet. This research has a purpose to describe about teaching materials used at MA Nurul Iman in Bandung, devise and develop a short story module based on the students’ needs. The developed module based on interpersonal intelligence. Research method uses 4 D development. This process consist of defining, devising, developing and disseminating process. Result of the research shows that the use of teaching materials are very limited and it is deemed lacking by the students and teachers. The use of the teaching materials are not based on the requirement yet and development teaching materials used in the school are still lacking. Devising module has been done based on requirements and interpersonal intelligence by maintaining content, presentation of the subject, language and reading and graphics aspects. The module designed is concerning to chose an example of a short story connected to environment and should be accompanied by picture which could stimulate the interpersonal intelligence of the students. Module trial result shows the use of the module give an impact and benefits with good predicate.